PENGARUH ROTASI KERJA, MOTIVASI KERJA DAN SEMANGAT KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN BIREUEN - Mulyadi; Ramli; Win (JURNAL KEBANGSAAN, 2023)
This study aims to explore further and provide empirical information about, the relationship and effect of job rotation, work motivation and work morale on the performance of the Education and Culture Office of Bireuen Aceh Regency. The results of the path analysis show, 1) There is a direct and indirect effect of job rotation on the performance of the employees of the Education and Culture Office of Bireuen Regency, which is 64.18%. 2) There is a direct and indirect effect of work motivation on the performance of the employees of the Education and Culture Office of Bireuen Regency, which is 32.82%. 3) There is a direct and indirect effect of morale on the performance of the employees of the Education and Culture Office of Bireuen Regency, which is 42.01%. 4) Simultaneously work rotation, work motivation and work spirit together affect the performance of the employees of the Bireuen Regency Education and Culture Office is 30.2%. While the rest (residual value) of the role of the variables that are not studied is 60.8%. The residual value shows that there are other factors that can affect employee performance variables such as work culture, organizational environment, compensation, leadership, communication and others.